Música e psicanálise: a afetação musical na vida psíquica - Luiz, Leonardo (2010)
This thesis deals with music and the musical choices from the viewpoint of psychoanalysis. I ve considered the questions of the actions related to the cultural industry and the manipulation of the phonographic industry due to the fact that both are factors that mould the subject and his personality. I take the pathway that some commentators of Freudian Psychoanalysis took which shows on what they based themselves to formulate theories that could ―talk‖ with the musical aspects of each individual. First I examine a dimension of the process of identification and the functioning of the masses that make the music come closer to the individual and vice-versa. Next, I present the aspects that feed the source of the identifications. I approach the way that some affective mechanisms happen and how each individual establishes his identifications which open the pathway to the emphasis given to the approach to musical questions and their psychological effects in the history of each subject. As the musical object is invisible and non-palpable, escaping what is tangible and identifying itself with the that can t uttered, therefore highly subjective, I also tried to answer how the (musical) sonorities affect this subjectivity. The pathways taken will show the role of the psychoanalytic listening that is capable of listening to the subject that is affected by any musical aspect. I identified the sole reason of the life history of each subject crossed by musical aspects which allows a pondered reflection about the idea that I ve named ―musical affects in the psychic life‖. The idea of the musical affects in the psychological life and how music and psyche relate to each other theoretically and in the private clinic of the psychoanalyst will be broadly discussed at the chapter that presents vignettes of three clients and their specific musical recollections and their usage in the psychoanalytic setting. Here I describe how the musical sonorities of each one of them contributed to the course of their own analysis presenting themselves as elements that mediate the psychological transformations and create original ways to bring meaning to a specific psychic situation